Risk factors for musculoskeletal pain among office workers - Kowalczyk, Anna; Kulczycka, Kinga; Stychno, Ewa; Chilimoniuk, Beata (Journal of Education, Health and Sport, 2018)
Musculoskeletal disorders occur with different frequency and intensity within particular occupational groups. On the basis of the research and observations carried out, the features of people and their living environment, which predispose to the development of disease changes within the locomotor system, were identified. They are divided into two categories: occupational risk factors and non occupational risk factors. The aim of this paper is to present the main risk factors for musculoskeletal pain among office workers. Early identification and knowledge of vulnerable people allows to plan and implement corrective and preventive actions at the stage when they have a chance to effectively limit, stop or even reverse the disease changes developing in these people.